Implementation of Character Education Empowerment Thematically, with Literacy Movement, and with Counseling Guidance at Public Preliminary School - Mustikaningrum, Galih; Joko Raharjo, Tri; Prihatin, Titi (Universitas Negeri Semarang, 2021)
In the 2013 curriculum in Indonesia, one of which is to instill character in students, so the school must make the right strategy. This research aims to describe the implementation of character education empowerment (CEE) thematically, with literacy movement and counseling guidance service. This research was carried out in a Public Primary School during the odd semester of the academic year 2020/2021. The subjects consisted of the principal, class teachers, and parents. The obtained data was from interview, documentation, and field observation. The applied data analysis consisted of data reduction, display, verification, and conclusion. The findings showed that CEE was done thematically by designing a specific plan. CEE with literacy movement invited learners to understand the learning materials and the surrounding environment. The CEE with counseling guidance was done with basic and responsive services and individual and preference plans. Every teacher invited learners to read, write, listen, and communicate carefully and accurately to the surrounding environment or during classroom learning. The hindrances occurred during the Coronavirus pandemic CEE with thematic used online learning.